2011
DOI: 10.3892/etm.2011.338
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum thymidine kinase 1 levels during chemotherapy correlate with objective response in patients with advanced gastric cancer

Abstract: Serum thymidine kinase 1 (STK1) is a reliable proliferation marker in most solid tumors, including gastric cancer. The aim of this study was to evaluate whether STK1 levels are related to the tumor response to chemotherapy and survival in advanced gastric cancer. The results showed that the average STK1 level in patients with gastric cancer (5.57±3.07 pM) was significantly higher than that in the healthy controls (1.12±0.57) (P<0.001). Among the 84 patients, the average STK1 level (6.02±3.12) in the 56 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…[30][31][32][33] Recently, TK1 has become the most widely tested serum marker of solid tumors, including gastric cancer, particularly with regard to monitoring the effect of tumor therapy, prognosis, and follow-up. 34 The decrease in TK1 levels after immunotherapy may be related to the inhibition of proliferation of tumor cells. In addition to TK1, the CTC level is a robust biomarker of the effects of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] Recently, TK1 has become the most widely tested serum marker of solid tumors, including gastric cancer, particularly with regard to monitoring the effect of tumor therapy, prognosis, and follow-up. 34 The decrease in TK1 levels after immunotherapy may be related to the inhibition of proliferation of tumor cells. In addition to TK1, the CTC level is a robust biomarker of the effects of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The new-generation STK1p concentration assay shows an area under the curve (AUC) value of 0.96 (18), and is a more reliable assay than the serum TK activity (19,20) and serum TK1 sandwich ELISA (21) assays. Low STK1p values are associated with a better prognosis (16,18,(22)(23)(24)(25)(26)(27). The STK1p marker is an independent prognostic factor for survival in CRC patients (n=504) (28).…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies showed significantly higher TK1 protein levels in sera from patients with solid tumors compared to healthy persons [ 23 , 24 ]. TK1 protein assays were found to be more sensitive than the TK1 activity assays for prognosis and treatment monitoring of patients with solid tumors [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%